Are the Boundaries Between Ordinary Jurisdiction and Arbitral Proceedings Blurring? The Intervention of Criminal Jurisdiction in the Heirs of the Sultan of Sulu vs. the Federation of Malaysia case - Fornaris Valls, Ignacio (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The contentious case of the Heirs of the Sultan of Sulu versus the Federation of Malaysia, culminating in the criminal conviction of an arbitrator in Spain, highlights critical issues surrounding the boundaries of judicial intervention in arbitration and the application of criminal law to resolve disputes between parties. This article explores the broader implications of the annulment of proceedings in the judicial appointment of arbitrators, underscoring the need to safeguard arbitral independence amidst a rising trend toward excessive judicial interference. Striking an appropriate balance between arbitration and ordinary jurisdiction is essential to uphold the legal principles governing both domains.